Effect of dispersants on microstructures of nano alpha alumina developed from aluminium dross waste - Sofian, Anis Sofia; Samat, Noorasikin; Meor sulaiman, Meor Yusoff (Trans Tech Publications, Switzerland, 2015)
This paper compares the effect of dispersants which are Sodium Laureth Sulfate (SLS)and distilled water (DW) on the crystallization, particle size distribution and morphological behavior of nano alpha Alumina (α-Al2O3) synthesized from Aluminium (Al) dross waste. The synthesizing of nano α-Al2O3 via wet milling method was performed using a planetary mill for 4 hours at a speed of 550 rpm. The nano α-Al2O3 powders with dispersants were characterized with xray diffraction (XRD), particle size analyzer (PSA) and transmission electron microscopy (TEM). XRD analysis shows the broadening and shifting of peaks after the sample was calcined at 1300 ̊C,indicating high crystallinity. The crystallite size of α-Al2O3 milled with SLS is also smaller than the α-Al2O3 milled with DW. These results are consistent with the PSA analysis in which the graphs displayed a symmetrical trend. Then, the PSA analysis is validated with TEM observation up to 100000x magnification, particularly for α-Al2O3 milled with SLS.